SURFACE TREATMENT OF SMALL DIAMETERS ON THE 16C20 MACHINE MACHINING OF SMALL DIAMETER SURFACES ON THE 16K20 LATHE - Oqyolova Nigora Inabidin qizi (Modern American Journals, 2025)
This article examines the process of workpiece positioning during the reaming of various deep holes. This process enhances surface cleanliness and ensures high processing quality. When forming deep holes with small diameters, it is advisable to use methods that provide high precision, surface smoothness, and improved machinability of parts while maintaining their hardness at a level of at least HRC≤445. Such methods include reaming and broaching.
Keywords: Reaming, Drilling, Taps, Counterbores, Boring Tools, Lathe Machines.